Creative Leadership and Stakeholder Engagement: Producer Collaboration Strategy in Preserving Traditional Arts Through the Documentary "Gemolong Pacelathon Theater - Muhamad Salim Al Ghofari; Kundori Kundori; Heriyanto Heriyanto; Joehanto DTW (eScience Humanity Journal, 2026)
This final project examines the producer’s role in building collaboration in the television documentary Teater Pacelathon Gemolong, which highlights the preservation of traditional performing arts in Gemolong, Sragen, Central Java. The author applied collaboration theory through both internal and external partnerships with the Teater Pacelathon Gemolong community, Kamera Space, Sakamata Studio, Selaras Coffee, and Wiby Rentcar to support the production requirements of the television documentary. The creative production process was carried out through field research, observation, interviews, and production coordination during the pre-production, production, and post-production stages. The results demonstrate that the implementation of collaborative practices enhanced production effectiveness, facilitated resource management, and supported the overall production process of the television documentary. This documentary not only documents the history and challenges faced by Teater Pacelathon Gemolong but also raises public awareness of the importance of preserving traditional cultural heritage. The author concludes that well-organized collaboration can contribute to the creation of an informative, educational, and engaging documentary that is relevant to contemporary Indonesian audiences.